Integrating network pharmacology and experimental validation to explore the effect and mechanism of AD-1 in the treatment of colorectal cancer - Li, Jiawei; Li, Fangfang; Zhao, Yuqing; Jin, Dan (Frontiers in Pharmacology, 2023)
20 (R)-25-methoxyl-dammarane-3β, 12β, 20-triol (AD-1), a novel ginsenoside isolated from stem and leaf of Panax Notoginseng, has anticancer activity against a variety of malignant tumors. However, the pharmacological mechanism of AD-1 on colorectal cancer (CRC) remains unclear. The purpose of this study was to verify the potential mechanism of action of AD-1 against CRC through network pharmacology and experiments. A total of 39 potential targets were obtained based on the intersection of AD-1 and CRC targets, and key genes were analyzed and identified from the PPI network using Cytoscape software. 39 targets were significantly enriched in 156 GO terms and 138 KEGG pathways, among which PI3K-Akt signaling pathway was identified as one of the most enriched pathways. Based on experimental results, AD-1 can inhibit the proliferation and migration of SW620 and HT-29 cells, and induce their apoptosis. Subsequently, the HPA and UALCAN databases showed that PI3K and Akt were highly expressed in CRC. AD-1 also decreased the expressions of PI3K and Akt. In summary, these results suggest that AD-1 can play an anti-tumor role by inducing cell apoptosis and regulating PI3K-Akt signaling pathway.